Pathological response of different molecular subtypes of locally advanced breast carcinoma to neoadjuvant chemotherapy - Nidhi Aley Alex; Sankar S; Saji Mary Varghese; Suresh Kumar K (Asian Journal of Medical Sciences, 2023)
Background: This study was done on modified radical mastectomy (MRM) specimens of patients with locally advanced breast carcinoma (LABC) who were categorized into molecular subgroups based on Immunohistochemistry and underwent neoadjuvant chemotherapy (NACT). The purpose of the study was to look for the pathological response of the tumor to the NACT. The molecular subtypes include Luminal A, Luminal B, Human epidermal growth factor receptor 2 (HER2) enriched, and triple negative. For HER2 enriched subtype, trastuzumab was also given along with the chemotherapy regimen. Aims and Objectives: The primary objective of this study is to find out the pathological complete response (pCR) in various molecular subgroups of breast carcinoma following NACT. The secondary objective is to describe the cellular changes in tumor tissue following NACT. Materials and Methods: This is a descriptive study done on MRM specimens of patients with LABC received in histopathology lab of Government Medical College, Kottayam to look for the pCR of the tumor following NACT. Gross examination and histopathology study of the specimen including axillary lymph nodes were done. The trucut biopsies of these cases with immunohistochemistry study were reviewed for confirming the grade and molecular subtype. pCR was assessed based on Chevallier system. Results: Of the 131 MRM specimens studied, overall pathologic complete response rate was 24.4% and the pathologic complete response rate in Luminal A subtype, Luminal B subtype, HER2 enriched tumors, triple negative tumors were 23.6%, 24%, 33%, and 20%, respectively. Conclusion: 33% of HER2 enriched subtype showed a pCR, i.e., no residual foci of neoplasm seen in the MRM specimens following NACT. Following NACT, change in tumor cellularity, changes in the morphology of neoplastic cells, changes in the surrounding breast tissue, and a change in grade of tumor were also noticed.